Internalisasi Nilai-Nilai Agama Islam dalam Pembelajaran IPS Berbasis Lingkungan Hidup - Nurizzati, Yeti; Binga Juanti (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study was motivated by the lack of integration between environmental issues and Islamic values in social studies (IPS) learning. Teachers often rely solely on textbooks and do not utilize environmental or religious-based school programs, resulting in convoluted material and low student awareness of environmental issues. This research aims to explore the internalization of Islamic values in environment-based IPS learning, the learning process itself, and the supporting and inhibiting factors in class VIII A at SMP Negeri 1 Plered. Using a qualitative descriptive approach, data were collected through observation, interviews, and document studies involving the principal, IPS and Islamic studies teachers, and students. The results show that the internalization of Islamic values has been implemented through environmental and religious programs, with the environment used as a learning medium. Supporting factors include school programs, while inhibiting factors involve low awareness among teachers and students to apply these values in daily life.